2005
DOI: 10.1007/s00439-005-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

Population stratification confounds genetic association studies among Latinos

Abstract: In the United States, asthma prevalence and mortality are the highest among Puerto Ricans and the lowest among Mexicans. Case-control association studies are a powerful strategy for identifying genes of modest effect in complex diseases. However, studies of complex disorders in admixed populations such as Latinos may be confounded by population stratification. We used ancestry informative markers (AIMs) to identify and correct for population stratification among Mexican and Puerto Rican subjects participating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
188
1
8

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 247 publications
(210 citation statements)
references
References 47 publications
13
188
1
8
Order By: Relevance
“…We have previously shown that there is evidence of substantial confounding from population stratification in association studies of asthma in Latino populations (Choudhry et al 2006). Here, we confirm our previous findings using a much larger set of AIMs (n = 2730) suggesting that any association study of asthma in Latino populations should be tested and corrected for population stratification.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We have previously shown that there is evidence of substantial confounding from population stratification in association studies of asthma in Latino populations (Choudhry et al 2006). Here, we confirm our previous findings using a much larger set of AIMs (n = 2730) suggesting that any association study of asthma in Latino populations should be tested and corrected for population stratification.…”
Section: Discussionsupporting
confidence: 88%
“…Although there are many potential explanations for this observation, including environmental and socioeconomic factors, one likely explanation is that the genetic predisposition to asthma differs among subgroups within the Latino population. Latinos are admixed and share varying proportions of West African, Native American and European ancestry (Choudhry et al 2006;Hanis et al 1991). The mixed ancestry of Latinos provides unique opportunities in epidemiological and genetic studies and may be useful in untangling complex gene-gene and gene-environment interactions in disease susceptibility Choudhry et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The study participants were mostly of Puerto Rican origin, who are a mix of European (predominant), Amerindian, and African American race. 15 The inclusion criteria for the parent study were: self-identified Hispanic ethnicity; age over 18 years; Spanish fluency; HIV seropositive and/or current drug use. Exclusion criteria were: pregnancy at recruitment; non-HIV associated malignancies; refusal to sign a consent form to release medical records; and chronic renal replacement therapy.…”
Section: Methodsmentioning
confidence: 99%
“…14,[18][19][20] Although one prominent study concluded that Puerto Rican Americans are similar to Mexican Americans with a lower frequency of hypertension compared with non-Hispanic EUR Americans 21 this interpretation has been questioned based on methodological issues 22 and one cross-sectional study found a 2.6-fold risk for systolic hypertension in Puerto Rican Americans compared with non-Hispanic EUR Americans. 23 In addition, the differences in admixture among these populations may explain why some 2 but not other studies 16,17 have suggested that HA have lower frequency of hypertension than non-Hispanic EUR American populations.…”
Section: Admixture Effects Hypertension In Women R Kosoy Et Almentioning
confidence: 99%